MyPertamina Application To Increase Consumer Engagement - Afniar Amelia Sinurat; Chandra Hendriyani; Fenny Damayanti (Fakultas Pendidikan Ekonomi dan Bisnis, 2022)
Abstract. The implementation of technology into the service process is a breakthrough to increase customer engagement which will create a sustainable competitive advantage for the company. The MyPertamina application made by a state-owned company is an innovation in the form of an e-wallet that is connected to LinkAja to make it easier for customers to transact at Pertamina gas stations on a cash-less basis. This study aims to analyze fintech services available at MyPertamina in increasing customer engagement. This research was conducted using qualitative research with a descriptive approach. Data collection techniques are carried out with a study of literature. The data obtained is primary data in the form of the number of MyPertamina consumers since its launch in August 2019 to April 2022. MyPertamina in increasing customer engagement has problems in implementing MyPertamina, namely that there are bugs such as the difficulty of obtaining otp codes and Pertamina officers do not fully understand the use of MyPertamina. For these problems, the MyPertamina development team should immediately fix the bugs contained in the application and the need to share knowledge about the use of MyPertamina to Pertamina officers so that the service can satisfy MyPertamina consumers. Keyword. e-wallet, customer engagement